D-(+)-Glucose-triggered metallogel to metallogel transition. Issue 32 (6th August 2020) - Mahendar, Chinthakuntla; Dixit, Manish Kumar; Kumar, Yeeshu; Dubey, Mrigendra
Abstract : The metallogel to metallogel transition triggered in response to a chemical reaction with d -(+)-glucose has been demonstrated. The conformational changes in the gelator p -H6 BAL and conductance properties during the transition were well studied. Abstract : A chiral metallogel (2% w/v, DMSO) has been obtained from a phenylboronic acid-tagged l -tartaric-based symmetrical ligand ( p -H6 BAL ) and LiOH. The metallogel to metallogel transition triggered in response to a chemical reaction with d -(+)-glucose has been fully characterized using UV-vis, circular dichroism, FESEM, 1 H NMR, ESI-Mass, rheology and impedance spectroscopies.